2014
DOI: 10.1007/s13277-014-2297-y
|View full text |Cite|
|
Sign up to set email alerts
|

Who benefits from hypofractionated radiation therapy for clinically localized prostate cancer: evidence from meta-analysis

Abstract: The aim of this study is to explore the oncological outcomes of hypofractionated radiotherapy for patients with prostate cancer. We systematically searched PubMed, Embase, and the Cochrane Library prior to April 2014 and references of relevant original papers and review articles. Unpublished data from meeting abstracts were supplemented. Studies comparing hypofractionated with conventionally fractionated radiotherapy (CFRT) on oncological outcomes of patients with clinically localized prostate cancer were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Multiple studies, including randomized clinical trials, have shown that increasing radiation dose for prostate cancer improves local tumor control and decreases metastasis [1]. Additionally, associated complication rates have been proven to be acceptable when advanced techniques such as intensity-modulated radiation therapy (IMRT) and image-guidance are used.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies, including randomized clinical trials, have shown that increasing radiation dose for prostate cancer improves local tumor control and decreases metastasis [1]. Additionally, associated complication rates have been proven to be acceptable when advanced techniques such as intensity-modulated radiation therapy (IMRT) and image-guidance are used.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other epithelial tumors it has been speculated that the α/β ratio of prostate cancer is less than that of the surrounding normal tissues. An α/β ratio means more low tumor sensitivity to the magnitude of the fraction, and therefore an increase in dose per fraction over 1.8 or 2.0 Gy (conventional fractionation) provides a therapeutic benefit [3,10]. The first suggestion that the α/β ratio for prostate cancer is about 1.5Gy was obtained from an analysis of the results by comparing patients with permanent seed implant brachytherapy dose of 145 Gy and another group treated with external beam radiotherapy (RTE) and conventional fractionation dose of 70-74 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 80-85% of cases are organ-confined [1]. The main prognostic factors for developing risk groups for prostate cancer include PSA, Gleason score and clinical stage, classified according to the criteria of D'amico at low, medium and high risk [2,3]. Several randomized trials have shown that increasing the dose of external radiation therapy with standard fractionation improves biochemical control in patients with localized prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies that analyzed the effects of dose escalation have shown a decrease in biochemical failure in low, intermediate and high risk prostate cancer. Although a recent meta-analysis studying the benefit of hypofractionated therapy has shown a significant decrease in bRFS only in high risk tumours [60], most of the studies have investigated the effect of the dose escalation among tumours with different clinicopathologic prognostic factors, and therefore, prospective randomized trials with stratification in different prognostic groups are needed to identify the group of patients that benefit most from this strategy. Furthermore, identification of new prostate cancer biomarkers associated to aggressiveness and recurrence may help to identify tumours with different α/β ratios that allow to prospectively investigate which patients are going to benefit most from the different fractionation schemes.…”
Section: Patient Selectionmentioning
confidence: 99%